Bagaço de azeitona na terminação de cordeiros em confinamento - Teixeira, William Soares (2022)
The present experiment aimed to evaluate the influence of the inclusion of increasing levels of olive pomace (OP) in substitution of corn silage (CS) as a roughage feed in the sheep diet. Nutrient intake, performance, ingestive behavior, economic viability of finishing and the lipid profile of meat from lambs in a feedlot system were evaluated. Thirty-five male lambs, not castrated, Texel x Ile de France crosses, weaned at 50±5 days of age, kept in individual pens were used. The treatments consisted of five levels of replacement of CS by OP, being 0%, 15%, 30%, 45% and 60%, based on dry matter (DM). A roughage: concentrate ratio of 50:50, on a DM basis, was used. The concentrate consisted of ground corn, soybean meal, limestone and common salt. The consumption of DM, MO, CP, NDF, CHT and NDT decreased linearly (P≤0.05) with the increase in the use of OP. The consumption of EE and ADF presented a quadratic result (P≤0.01) with the increase of OP levels. The average daily weight gain (DWG) was influenced in a decreasing linear way by the inclusion of OP in the diet (P≤0.05). Regarding the ingestive behavior, the time spent in feeding (ALIM) was influenced in a quadratic way (P≤0.05), while the rumination (RUM) and idleness in a cubic way (P≤0.05) with the increase of BA in the diets. The increase in the level of OP in the diet linearly reduced (P≤0.05) the daily feed costs and provided a linear increase (P≤0.05) in the profit obtained per kilogram of lamb live weight gain. As for the lipid profile of the lamb meat, the increase in the replacement of CS by OP linearly reduced (P≤0.05) the levels of C16:0, while it linearly increased (P≤0.05) the concentrations of C18:0, C18:1 c11 of the longissimus dorsi muscle of lambs in feedlot. The increase in the level of OP in the diets increased the concentration of desirable fatty acids (DFA) (C18:0 + monounsaturated + polyunsaturated) in lamb meat. In a concentrated roughage ratio of 50:50, the weight gain drops linearly, however, OP can be used as roughage in place of SM up to the proportion of 60%, since the increase in the level of use of this residue reduces daily feed costs and providing an increase in the profit obtained per kilogram of lamb live weight gain and increases DFA values improving some aspects of the lipid profile of the animals.